Metode Tafsir Kontemporer - Syufa'at Syufa'at (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Contemporary discussion among Moslem scholars about the way to understand, interprest, and apply al-Qur’an in daily life is based on a belief that al Qur’an as the last bible of God’s revelation can be adjusted at anytime and anywhere. It accordance to understand God’s revelation objectively, moslems have to concern about the language and socio-cultural setting factors.